RANCANG BANGUN PENERAPAN CVT VARIO 110 PADA MESIN CUCI PENGGERAK MEKANIS KAPASITAS MAKSIMAL 7 KG - Zaenudin; Haris, Oscar (Universitas Nusa Putra, 2021)
Washing is an activity that is done every day by housewives, young people, and is done by anyone, so it takes time to do washing activities, especially housewives who have so many jobs at home that washing is quite a heavy job for housewives. ladder. The design of the application of the CVT Vario 110 on a mechanical driving washing machine with a maximum capacity of 7 kg is expected to be a solution to the problems of housewives in washing. The method used in this research is by design, Design Analysis and continued with the fabrication process of the design results, and testing the washing machine that has been made. The results of the calculation of washing and drying rotations at the front sprocket are 91.6 rpm, the rear sprocket is 436.3 rpm, and the tube rotation is 127.1 rpm. Then tested using a tachometer with the results of testing the front sprocket 86.3 rpm, rear sprocket 294.6 rpm, primary pulley (CVT) 294.6 rpm, secondary pulley (CVT) 145.5 rpm, and tube (tube) 127, 1 rpm. Based on the test results, this washing machine is capable of washing up to a capacity of 7 kg so it is suitable for use in helping housewives wash their jobs.